If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(5 + -1x) = -4(x + -11) (5 * 7 + -1x * 7) = -4(x + -11) (35 + -7x) = -4(x + -11) Reorder the terms: 35 + -7x = -4(-11 + x) 35 + -7x = (-11 * -4 + x * -4) 35 + -7x = (44 + -4x) Solving 35 + -7x = 44 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 35 + -7x + 4x = 44 + -4x + 4x Combine like terms: -7x + 4x = -3x 35 + -3x = 44 + -4x + 4x Combine like terms: -4x + 4x = 0 35 + -3x = 44 + 0 35 + -3x = 44 Add '-35' to each side of the equation. 35 + -35 + -3x = 44 + -35 Combine like terms: 35 + -35 = 0 0 + -3x = 44 + -35 -3x = 44 + -35 Combine like terms: 44 + -35 = 9 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| 3x^2+4x+1=65 | | a/2+a/2=3a+14 | | 10x^2-11x-12=0 | | 25t-5t^2-120=0 | | 5t^2-20t+15=0 | | 2x^3-3x-12x=0 | | 1+5x=19-x | | 9x+5y+6z-5x+4z-6y= | | x(x-10)=-21 | | Q=9xv | | 60=70-x | | 3s+18=3(s+6) | | -10(3y-5)=-30Y+50 | | 7x+2(x+5)= | | 8(9+5*3)= | | 21y+6=12 | | 7x+2(x+2)= | | 12+8=52 | | 0=x^4-2x^2+3 | | 0=4x^3+3x^2 | | 8(x+4)-4=4x-1 | | 5a+30=10a+5 | | 9m(4-3m)=0 | | -4(4a+8)=-16a-32 | | -4sinx+2=0 | | 1+11x=-29+x | | -3(-10+15r)=5(-9r+3) | | 5x+7(3x+2)=(4x+1) | | 25-.5n=10 | | 33-5x=13-7x | | 9m-13=58 | | 9m-23=53 |